151 Falls in the United Kingdom: Magnitude, Risk, Disparities, and Solutions. (20th December 2019) - Frith, James; Robinson, Lisa; Newton, Julia
Abstract: In the UK each year there are over 250, 000 emergency hospital admissions due to falls, costing £4.4 billion for falls-related fractures alone. To help reduce pressure on the NHS, the UK Fire Service are now providing home safety checks which include a review of falls hazards, provision of falls and loneliness advice and in some cases, immediate provision of aids such as grab rails. It is yet to be seen whether this will translate into a reduction in falls but it appears that the trust people place in the Fire Service is resulting in an uptake of falls prevention advice. Although we have reasonably good evidence that multifactorial falls interventions reduce the rate of falls, they are resource intensive and do not reduce the risk of falls. In contrast, exercise interventions reduce both the rate and the risk of falls and can be delivered in a group setting; however uptake and adherence is low. In an attempt to encourage local care providers to invest in falls prevention exercise, Public Health England created a Return-of-Investment tool (available online) for local commissioners to calculate the anticipated cost savings by investing in falls prevention exercise programmes. A recent, novel approach to falls prevention developed in the UK is a Massive Open Online Course (MOOC). This is a free, open-access, online course open to anyone with access to the Internet. The purpose of the 'Ageing Well: Falls' MOOC is to educate people about falls prevention and empower them to take action. In five years, the course has educated over 10, 000 people from over 100 countries worldwide. One survey revealed that 95% of learners felt more empowered to manage their falls risk, with an increase in confidence to engage in falls prevention behaviours but also an increase in confidence to seek help for falls.